PENGARUH PERSEPSI SISWA TENTANG BRAND IMAGE KAMPUS, KONDISI SOSIAL EKONOMI ORANG TUA DAN TINGKAT KEMAMPUAN AKADEMIK SISWA TERHADAP MINAT MELANJUTKAN KE PERGURUAN TINGGI - Yasrul Adi Firmansyah; Rusno Rusno; Riril Mardiana Firdaus (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2018)
The purpose of the research is to reveal the influence of students' perception about the campus brand image, the socioeconomic condition of the parents and the level of academic ability on the interest of continuing to university. The research used quantitative approach with explanatory research type. The population numbered 273 students in MAN Gondanglegi. The sample of 83 students is determined using proportional random sampling. Data collection techniques used questionnaires and documentation. Based on the results of the analysis can be drawn some conclusions include: there is the influence of brand image on the interest of continuing to college, there is influence of socio-economic conditions of parents on the interest of continuing to college, there is influence of students' academic ability on the interest to continue to college, simultaneous brand image of campus, condition of socio-economic of parents and level of academic ability to interest to continue to university and value of R2 equal to 0,955 which means brand image of campus, condition of socio-economic of parents and level of academic ability influence 95,5% to interest to continue to college grade XII in MAN Gondanglegi.